Media interaction with the public in emergency situations : four case studies - Berry, LaVerle Bennette, 1942- (Library of Congress, Federal Research Division, 1999)
"The following report provides an analysis of media coverage of four major emergency situations in the United States and the impact of that coverage on the public. The situations analyzed are the Three Mile Island nuclear accident (1979), the Los Angeles riots (1992), the World Trade Center bombing (1993), and the Oklahoma City bombing (1995). Each study consists of a chronology of events followed by a discussion of the interaction of the media and the public in that particular situation. Emphasis is upon the initial hours or days of each event. -- Print and television coverage was analyzed in each study; radio coverage was analyzed in one instance. The conclusion discusses several themes that emerge from a comparison of the role of the media in these emergencies. Sources consulted appear in the bibliography at the end of the report."